Chip making's wet new world. - Geppert, L. (IEEE spectrum)
Putting a drop of water between the lens and the silicon wafer allows a system to resolve lines a few hundred atoms wide. Researchers are counting on it to lift the technology from its last legs and carry it through the end of the decade.